Marsilio Ficino, Francesco Cavalli en muziek als remedie voor liefdesverdriet - Prins, Jacomien (Incontri. Rivista europea di studi italiani, 2016)
Marsilio Ficino, Francesco Cavalli and Music as Remedy for Lovesickness In this article, the philosopher Marsilio Ficino (1433-1499) and the composer Francesco Cavalli (1602-1676) are presented as belonging to one and the same universe of discourse, in which music, love, and the imagination play a fundamental role. Ficino’s Neoplatonic theory of love plays a central role in his philosophy. He defines love as the desire for beauty. Beautiful things such as harmonious music inspire the soul with love. When music is loved properly, the lover distances himself from the sensible world, focuses his attention on his soul, and thus ultimately finds his end in God. However, if the soul loves improperly and becomes fixated on the sensual beauty of music, this results in lovesickness. Thus, for Ficino, the proper application of love and music lie at the heart of human happiness. A secularized echo of this theory can be heard in the Cavalli’s opera Artemisia.